Enhancement of hardness, modulus and fracture toughness of the tetragonal (Fe, Cr)2B and orthorhombic (Cr, Fe)2B phases with addition of Cr. (15th October 2018) - Lentz, Jonathan; Röttger, Arne; Großwendt, Felix; Theisen, Werner
Abstract: This study analyzes the influence of Cr content on hardness H, elastic modulus E and fracture toughness KIC of the M2 B boride by means of nanoindentation experiments. Additionally, properties of the Fe3 (C, B) phase are determined. Samples of the M2 B phase are casted and microstructurally characterized by means of scanning electron microscopy, energy dispersive spectroscopy and X-ray diffraction. At a Cr content higher than 14.7 atom% the M2 B phase transforms from tetragonal into orthorhombic structure. The tetragonal M2 B type possesses an optimum of H (21 ± 1 GPa), E (373 ± 6) GPa and KIC (3.5 ± 0.7 MPa m ) at 4–5 atom% Cr. The hardness, modulus and toughness of the orthorhombic M2 B phase increase with Cr content and reach values of H = 27 ± 0.7 GPa, E = 473 ± 9 of and KIC  = 3.26 ± 0.8 MPa m at maximal investigated Cr content of 55 atom%. The hardness of the M2 B phases decreases around 2.3–3.2 GPa as a function of indentation depth, which is known as the indentation size effect. Hardness and fracture toughness of M2 B phase outperform conventionally used M7 C3 carbides and are similar to MC-carbides. Findings can be used in novel alloying approaches in order to optimize the performance and reduce cost of tool steels. Graphical abstract: Highlights: Exceeding 14.7 atom% Cr, the tetragonal M2 B transforms to orthorhombic structure with 23.2 up to 55.0 atom% Cr. Tetragonal M2 B displays a maximum of hardness (21.5 GPa), modulus (373 GPa) and toughness (3.5 MPam) at 4-5 atom% Cr. Additions up to 55 atom% Cr in orthorhombic M2 B enhance the hardness (27 GPa), modulus (473 GPa) and toughness (3.26 MPa m ) Mechanical properties of M2 B borides exceed those of M7 C3 ; for high Cr content equaling the properties of monocarbides.